Vacuum‐Assisted Preparation of High‐Quality Quasi‐2D Perovskite Thin Films for Large‐Area Light‐Emitting Diodes. (7th October 2021) - Chen, Chaoran; Zeng, Linxiang; Jiang, Zhengyan; Xu, Zhenhua; Chen, Yijun; Wang, Zhen; Chen, Shi; Xu, Baomin; Mai, Yaohua; Guo, Fei
Abstract: Recent years have witnessed marked progress in the electroluminescence efficiency of perovskite‐based light emitting diodes (PeLEDs). Nevertheless, the majority of highly efficient devices feature only several square millimeters with the perovskite emitting layers deposited by nonscalable methods, which hinders their intriguing application in large‐area lightings and displays. Here, a robust crystallization protocol is devised for the deposition of high‐quality perovskite emitting layers by blade coating. Central to this method is the deployment of a vacuum process to the freshly coated precursor film, thereby achieving controllable crystallization kinetics by decoupling precursor deposition and the subsequent thermal annealing. Accordingly, dense and uniform perovskite thin films with efficient energy funneling among the evenly distributed 2D and 3D phases are obtained. PeLED devices based on the vacuum‐processed quasi‐2D cesium lead tribromide layers achieve high external quantum efficiencies of 8.24% and 6.12% on active areas of 0.12 and 1 cm 2, respectively. The scalability of the technology is further demonstrated by fabricating a 3.5 × 3.5 cm 2 device with bright and uniform emitting characteristic. This work offers a viable approach for further advancing the performance of large‐area PeLEDs by scalable methods. Abstract : An effective crystallization protocol for scalable deposition of quasi‐2D perovskite emitting films is reported. Central to the technology is the deployment of a vacuum quenching process to the precursor film, which results in uniform and dense perovskite films with high photoluminescence efficiency. Light‐emitting diode devices based on the blade‐coated perovskite films yield a high efficiency of 8.24%.